RANCANG BANGUN ALAT PENGERING IKAN TIPE RAK MENGGUNAKAN KOLEKTOR SURYA - Sophyan, Nur Fadhilah; Ihsan, Ihsan; Sahara, Sahara (JFT: Jurnal Fisika dan Terapannya, 2016)
This research aims to design and produce the model design of the dryer rack type fish using solar collectors with the addition of a blower 1 unit’s maximum temperature 49˚ C, dimension 216666 with a capacity of 3 kg. The result of test 1, test 2, and 3 for 3 day test has been obtained an efficiency of 32,16 % greater than the manual drying efficiency of 5,4%. While in testing the quality of dried anchovies dried using solar collectors based on quality standards of dried anchovoies (SNI 01- 2708-1992) is not accordance with the prescribed standards in terms of microbiological bacteria mold furthermore, for testing chemically moisture content, ash content, and ash content insoluble in acid is still in accordance with (SNI 01- 2708-1992). Keywords: Anchovies, Efficiency, Plan, Shelf type, Solar collectors